Pengaruh Perasaan Insecure Terhadap Minat dan Hasil Belajar pada Mata Pelajaran Matematika Siswa Kelas V SD Al-Irsyad Kota Sorong - Sri Sujiyanti (MISOOL: Jurnal Pendidikan Dasar, 2023)
The aim of this research is to determine the influence of feelings of insecurity on interest and learning outcomes in mathematics subjects. There are many things that can cause someone to feel insecure internal and external factors. In this study, feelings of insecurity were felt studied, namely students' self-confidence regarding interest and learning outcomes in the eyes mathematics lessons for fifth grade students at SD Al-Irsyad, Sorong City. This research designed with a quantitative approach with a sample size of 76 students. Technique data collection using Saturated Samples. As well as using simple and multiple linear regression analysis as a data analysis method, technique The data collection instruments used were questionnaires and documentation.